Is Caton–Deschamps Index Reliable and Reproducible in Preoperative Assessment of Patellar Height for Patellar Instability Surgery? - Elisa Giacomina Pandini; Pierluigi Pironti; Davide Maria Maggioni; Lorenzo Impieri; Cristiana Balbino; Nicola Manta; Marco Viganò; Laura Mangiavini; Roberto D’Anchise (Applied Sciences, 2022)
The patellar height measurement is fundamental for surgical planning in patellar instability. The Caton–Deschamps index (CDI) is a widely employed method, but a gold standard is still lacking. The aim of this study was to evaluate the reliability and reproducibility of the CDI in a patellar height assessment and to hypothesize its employment in the preoperative planning of patellar stabilization surgery. A total of 29 cases of recurrent patellar instability undergoing surgical treatment were analyzed. The preoperative and postoperative CDI were measured by six different raters (three seniors and three juniors). The interclass correlation coefficient (ICC) of the six raters was calculated to evaluate the interobserver agreement. The seniors’ and juniors’ measurements were compared to assess the CDI reproducibility. The Fleiss kappa was calculated among the six raters to estimate the agreement in favor of an anterior tibial apophysis (ATA) transposition surgery. This study shows excellent absolute agreement in terms of the ICC for the raters’ average and for single raters as units, both preoperatively (p < 0.001) and postoperatively (p < 0.001). The agreement of the surgical choice between the six observers corresponds to “substantial agreement”. This study demonstrates that the CDI is reliable and reproducible, and it could represent a valuable tool in the clinical assessment, treatment choice and pre-surgical planning of patellar instability surgery.